2023
DOI: 10.1021/acs.langmuir.3c00297
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cellulose Fiber-Derived Photothermal Aerogel for Efficient and Sustainable Solar Desalination

Abstract: Aerogels are becoming a promising platform to fabricate photothermal materials for use in solar steam generation (SSG), which have remarkable application potential in solar desalination, due to their excellent thermal management, salt resistance, and considerable water evaporation rate. In this work, a novel photothermal material is fabricated by forming a suspension between sugarcane bagasse fibers (SBF) and poly(vinyl alcohol), tannic acid (TA), and Fe 3+ solutions via hydrogen bonds of hydroxyl groups. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Figure 4f shows the water transport rate of the aerogel, and the aerogel end is vertically contacted to the water surface to record the time required for the water to rise to 20 mm. It can be seen that the water transport rate of the pure CS aerogel is 1.69 mm s −1 , while that of the PCS with 30 wt% POSS reaches 2.67 mm s −1 , which is higher than the other reported water transport layer [59,60]. The enhanced water transport rate may be due to the introduction of hydrophilic hydroxyl groups in the chain EP-POSS cross-linked with Figure 4f shows the water transport rate of the aerogel, and the aerogel end is vertically contacted to the water surface to record the time required for the water to rise to 20 mm.…”
Section: Water Transport Properties Of Pcsmentioning
confidence: 67%
“…Figure 4f shows the water transport rate of the aerogel, and the aerogel end is vertically contacted to the water surface to record the time required for the water to rise to 20 mm. It can be seen that the water transport rate of the pure CS aerogel is 1.69 mm s −1 , while that of the PCS with 30 wt% POSS reaches 2.67 mm s −1 , which is higher than the other reported water transport layer [59,60]. The enhanced water transport rate may be due to the introduction of hydrophilic hydroxyl groups in the chain EP-POSS cross-linked with Figure 4f shows the water transport rate of the aerogel, and the aerogel end is vertically contacted to the water surface to record the time required for the water to rise to 20 mm.…”
Section: Water Transport Properties Of Pcsmentioning
confidence: 67%
“…Olivernesaraj and Sethuramalingam [2] proved that a rough surface structure could increase the light-trapping effect. Nguyen et al [3] and Zhang et al [4] demonstrated that porous structures increased the light-trapping effect. Ultimately, the light-trapping effect increased the absorbance and decreased the reflectivity of absorber materials [5].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, studies have been reported, such as Politano et al, prepared a nanostructured photothermal membrane distillation device consisting of a polymer with metallic nanoparticles, and Cao et al showed a superhydrophobic fabric with PVA/GO hydrogel self-assembly for an interfacial photothermal device of desalination and pollutant removal. , Similarly, Huang et al reported a self-floating bilayer photothermal paper made up of MWCNT and polyphenylene sulfide for rapid transportation of water and heat localization . Nguyen et al used sugar cane bagasse fiber aerogel-based photothermal (SBFAP) with its 3D interconnected porous microstructure for seawater desalination . Yang et al creatively designed a mass transfer bridge (MTB) architecture with a high salt rejection capacity .…”
Section: Introductionmentioning
confidence: 99%